2017
DOI: 10.3906/sag-1702-152
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of immunohistochemistry between core needle biopsy and surgical resection of breast cancer

Abstract: Background/aim: The purpose of this study was to evaluate the concordance of immunohistochemical (IHC) parameters of breast lesions between the core needle biopsy (CNB) and the surgical resection specimen.Materials and methods: CNB and resection specimens of female patients were retrospectively analyzed. ER, PR, HER-2, and Ki-67 parameters were compared for each patient. A total of 284 cases were assessed. Forty-one and 48 cases were excluded from the HER-2 and Ki-67 examinations, respectively, because the CNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Onestep discordance was 26% (13/50), and there was no twostep discordance. To investigate the low and midrange-risk categories, we also applied low (< 11), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and high (≥ 26) cutoffs, and the RS concordance between paired resection specimens and CNBs as categorical variables was 72%. A total of 14 tumours showed one-step discordance; similarly, there was still no two-step discordance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Onestep discordance was 26% (13/50), and there was no twostep discordance. To investigate the low and midrange-risk categories, we also applied low (< 11), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and high (≥ 26) cutoffs, and the RS concordance between paired resection specimens and CNBs as categorical variables was 72%. A total of 14 tumours showed one-step discordance; similarly, there was still no two-step discordance.…”
Section: Discussionmentioning
confidence: 99%
“…RS, ranging from 0 to 100, was derived from the reference-normalized expression measurements for the 16 cancer-related genes. Patients were then categorized into low-risk (< 18), intermediate-risk (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high-risk (≥ 31) groups [12]. We also investigated low-and midrange-risk groups as follows: low (< 11), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and high (≥ 26) [39][40][41].…”
Section: Rna Extraction Amplification and Gene Expression Analysis By Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of US elastography for the diagnosis of breast lesions is promising, especially in BIRADS 4 lesions. Previous studies have reported that the addition of elastography to B‐mode US increased the sensitivity of the malignant benign distinction of BIRADS 4 lesions by 96% and increased the specificity of this distinction by up to 95% 18‐22 . Factors such as cellular activation of the tumor, apoptosis, amounts of fibroblasts and fibrosis, changes in the extracellular matrix, collagen structure, integrin, and focal adhesion kinase increase the stiffness of the tissues in malignant tumors 16,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many advantages of core‐needle biopsy, it does not always completely and consistently reflect the biological features of the examined tumor due to intratumoral heterogeneity and methodological flaws. Previous studies have shown that consistency after resection by biopsy decreases to 77.8% for ER, 69% for PR, and 60% for HER2 18‐22 . Elastography‐based biopsy, which has been practiced for years in the diagnosis of prostate cancer, increases sensitivity as well as specificity and reduces the need for re‐biopsy 23 .…”
Section: Introductionmentioning
confidence: 99%